The Effect of Substantive Parameters On The Efficiency Of Archimedes Screw Microhydro Power: A Review - Nurul Suraya, Azahari; N. M. M., Ammar; Ummu Kulthum, Jamaludin (2015)
Due to the increasing demands in electricity and decreasing in fossil fuels sources, then hydropower are being developed and most of the project involve with large dams construction and may cause the people live surrounding to be flooded. Hence, the construction of Archimedes screw runner blade turbine can be the best option to generate energy without cause too much environmental impact like a fish friendly turbine and low maintenance cost. This review focus on the parameters that affected the performance of turbine. Besides the review also presented a methodologies based on parameters studied by previous researcher and from that review, it has been found that the uses of external parameter have an effect on the internal parameter in terms of efficiency. In further investigation, another parameter such as gap leakage, velocity of water, blade thickness should be considered to investigate the relationship of efficiency.